Case report: Improving quality of care in Kazakhstan institutions - McCall, Robert B.; Groark, Christina J.; Jappar, Akbota; Muhamedrahimov, Rifkat J.; Palmov, Oleg I.; Hawk, Brandi N.; Chen, Abigail P.; Spear, Caitlin F.; Mason, Larisa (Frontiers in Psychology, 2022)
This project is a community case study implemented by local professionals and caregivers to improve the quality of caregiving in two Kazakhstan institutions for infants and toddlers. Local professionals first received comprehensive training by an international team experienced in relevant research-based practices, and then the locals trained institutional staff. Over nearly 2 years, one institution progressively implemented changes in three wards and the other institution in one ward. The changes attempted to make the institution more family-like (e.g., smaller groups and fewer and more consistent caregivers) and caregivers behave more parent-like (e.g., more warm, sensitive, responsive interactions and relationships) without changing nutrition or medical care. Of the 45 children given some exposure to the emerging new wards, 11 experienced the fully revised wards for at least 4 months during their first 2 years of life. They displayed substantial increases in their physical growth, especially those entering in their first year of life, in contrast to the unchanging developmental patterns of 165 children who were reared in the two institutions before the ward changes were made. Physical growth is a commonly used standard of developmental well-being in institutions. Research shows it is sensitive to infants' psychosocial environment, and improvements in physical growth are related to children's cognitive and social-emotional development. Although this pilot community case study had only a few infants fully exposed to the complete ward changes and lacked characteristics of a research experiment, these results are consistent with children's developmental improvements reported in larger scientific studies of similar interventions. This project is an example of how some research-based practices are likely to be implemented in communities in the future. Specifically, it shows that local communities can successfully improve the rearing conditions within institutions, which improve the children's development, and may contribute to the success of their subsequent foster placement and adoption.